Substrate specificity provides insights into the sugar donor recognition mechanism of O-GlcNAc transferase (OGT). - Xiaofeng Ma; Pi Liu; Hui Yan; Hong Sun; Xiaoyan Liu; Feng Zhou; Lei Li; Yi Chen; Musleh M Muthana; Xi Chen; Peng G Wang; Lianwen Zhang (PLoS ONE, 2013)
O-Linked β-N-acetylglucosaminyl transferase (OGT) plays an important role in the glycosylation of proteins, which is involved in various cellular events. In human, three isoforms of OGT (short OGT [sOGT]; mitochondrial OGT [mOGT]; and nucleocytoplasmic OGT [ncOGT]) share the same catalytic domain, implying that they might adopt a similar catalytic mechanism, including sugar donor recognition. In this work, the sugar-nucleotide tolerance of sOGT was investigated. Among a series of uridine 5'-diphosphate-N-acetylglucosamine (UDP-GlcNAc) analogs tested using the casein kinase II (CKII) peptide as the sugar acceptor, four compounds could be used by sOGT, including UDP-6-deoxy-GlcNAc, UDP-GlcNPr, UDP-6-deoxy-GalNAc and UDP-4-deoxy-GlcNAc. Determined values of Km showed that the substitution of the N-acyl group, deoxy modification of C6/C4-OH or epimerization of C4-OH of the GlcNAc in UDP-GlcNAc decreased its affinity to sOGT. A molecular docking study combined with site-directed mutagenesis indicated that the backbone carbonyl oxygen of Leu653 and the hydroxyl group of Thr560 in sOGT contributed to the recognition of the sugar moiety via hydrogen bonds. The close vicinity between Met501 and the N-acyl group of GlcNPr, as well as the hydrophobic environment near Met501, were responsible for the selective binding of UDP-GlcNPr. These findings illustrate the interaction of OGT and sugar nucleotide donor, providing insights into the OGT catalytic mechanism.